IMPLEMENTATION OF LESSON STUDY TO IMPROVE UNDERSTANDING STUDENTS STUDY PGSD BASIC CONCEPTS IN SCIENCE ADVANCED - Faizah M.Nur; Muthmainnah Muthmainnah; Sarah Fazilla (Jurnal Pendidikan Almuslim, 2016)
This article aims to assess and monitor the implementation of lesson study course Basic Concepts in Science, focused further to see the quality of the learning process for the faculty implemented and problems faced by teachers in an effort to improve the professionalism of teachers as educators as well as expected to enhance students' understanding of the material delivered by lecturers. Lesson study is a model of professional development of educators through collaborative learning and ongoing assessment to build a learning community. Lesson study implementation phases of planning, implementation, observation and reflection are implemented in 4 cycles with matter waves, wave propagation, optical instruments and lenses. Implementation results show that there are various problems that can reduce student interest in learning, such as lack of faculty approach taken in controlling students when the discussion took place and the lack of use of media and learning resources associated with the material. Based on the results of a reflection of cycle 1 to cycle 3, it is seen that the interest of students in cycle 4 for the better, where enthusiastic students in a better expression and active as well as more disciplined and respectful during the learning process takes place. The results of these activities proved that the implementation of lesson study can improve student comprehension of the material provided lecturers. So expect this activity to continue to be done on an ongoing basis in order to improve the professionalism of lecturers in their duties as educators. Keywords: Implementation, Understanding, lesson study